ANALISIS EFEKTIVITAS MODEL PEMBELAJARAN BLENDED LEARNING DITINJAU DARI HASIL BELAJAR GEOMETRI MAHASISWA GURU SEKOLAH DASAR - Asri Fauzi; Aisa Nikmah Rahmatih; Linda Feni Haryati (COLLASE (Creative of Learning Students Elementary Education), 2022)
The purpose of this study was to analyze the effectiveness of the blended learning model in terms of student geometry learning outcomes. This type of research is a quasi-experimental quantitative research with a one-group pretest-posttest design. The sample of this research was 36 students who were taken based on cluster random sampling technique. The data collection instrument in this study used multiple-choice questions as many as 20 mathematics questions on geometry material. The data analysis techniques were normality test, difference test in the average pretest and posttest with the Paired Samples Test statistical test, the test for the increase in the pretest result with the posttest (N-Gain), and finally the effect size test. The results showed that the pretest and posttest data were normally distributed. The paired sample test shows the results of sig. (0.043) <0.05, it means that there is a difference between the average pretest and posttest scores. Then the n-gain test was carried out with a score of 0.196 which was in the low category. This means that the pretest and posttest scores have a low level of improvement. And the results of the last test with an effect size test with a score of d = 0.47, which means that the blended learning model has a weak effect on student geometry learning outcomes.